Free‐Breathing Ungated Radial Simultaneous Multi‐Slice Cardiac T1 Mapping - Le, Johnathan V.; Mendes, Jason K.; Sideris, Konstantinos; Bieging, Erik; Carter, Spencer; Stehlik, Josef; DiBella, Edward V. R.; Adluru, Ganesh (Journal of magnetic resonance imaging, 2025)
Modified Look-Locker imaging (MOLLI) T1 mapping sequences are acquired during breath-holding and require ECG gating with consistent R-R intervals, which is problematic for patients with atrial fibrillation (AF). Consequently, there is a need for a free-breathing and ungated framework for cardiac T1 mapping. To develop and evaluate a free-breathing ungated radial simultaneous multi-slice (SMS) cardiac T1 mapping (FURST) framework. Retrospective, nonconsecutive cohort study. Twenty-four datasets from 17 canine and 7 human subjects (4 males, years; 3 females, years). Canines were from studies involving AF induction and ablation treatment. The human population included separate subjects with suspected microvascular disease, acute coronary syndrome with persistent AF, and transthyretin amyloidosis with persistent AF. The remaining human subjects were healthy volunteers. Pre- and post-contrast T1 mapping with the free-breathing and ungated SMS inversion recovery sequence with gradient echo readout and with conventional MOLLI sequences at 1.5 T and 3.0 T. MOLLI and FURST were acquired in all subjects, and American Heart Association (AHA) segmentation was used for segment-wise analysis. Pre-contrast T1, post-contrast T1, and ECV were analyzed using correlation and Bland-Altman plots in 13 canines and 7 human subjects. T1 difference box plots for repeated acquisitions in four canine subjects were used to assess reproducibility. The PIQUE image quality metric was used to evaluate the perceptual quality of T1 maps. Paired t-tests were used for all comparisons between FURST and MOLLI, with indicating statistical significance. There were no significant differences between FURST and MOLLI pre-contrast T1 reproducibility ( and , ), FURST and MOLLI ECV ( and , ), or FURST and MOLLI PIQUE scores ( and , ). The ECV mean difference was with . FURST had similar quality pre-contrast T1, post-contrast T1, and ECV maps and similar reproducibility compared to MOLLI. 3 TECHNICAL EFFICACY: 1.